Geotechnical Aspects of Underground Construction in Soft Ground IX : proceedings of the 9th International Symposium on Geotechnical Aspects of Underground Construction in Soft Grounds (IS-São Paulo 2017), April 4-6, 2017, São Paulo, Brazil /: proceedings of the 9th International Symposium on Geotechnical Aspects of Underground Construction in Soft Grounds (IS-São Paulo 2017), April 4-6, 2017, São Paulo, Brazil. (2017) - Unknown
No abstract available